2023
DOI: 10.1021/acsomega.2c05815
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Facts of Effective Electromagnetic Interference Shielding Materials: A Review

Abstract: Electromagnetic interference (EMI) shielding effectiveness (SE) systems have received immense attention from researchers owing to the rapid development in electronics and telecommunications, which is an alarming matter in our modern society. This radiation can damage the performance of EM devices and may harmfully affect animal/human health. The harmonious utilization of magnetic alloys and conducting but nonmagnetic materials (such as carbon/graphene) is a practical approach toward EMI SE. This review is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…According to the electromagnetic theory, it can be known that the conductivity of materials has a critical impact on its electromagnetic shielding performance in general, since studies have shown that the value of RL increases with the increase of conductivity. 37 , 38 Therefore, the conductivity of GC/C films was tested first as shown in Figure 3 C. The graphene/carbon nanofiber composite film (GC/C-1) prepared by scraping and coating method showed excellent conductivity, which can reach 1000 S/cm. With the increase of the total number of alternating layers, the conductivity of the film shows a gradual decline, which is mainly because the increase of pores in the porous carbon alternating layer leads to the decrease of conductive path, which affects the increase of resistance caused by the free movement of electrons.…”
Section: Discussionmentioning
confidence: 99%
“…According to the electromagnetic theory, it can be known that the conductivity of materials has a critical impact on its electromagnetic shielding performance in general, since studies have shown that the value of RL increases with the increase of conductivity. 37 , 38 Therefore, the conductivity of GC/C films was tested first as shown in Figure 3 C. The graphene/carbon nanofiber composite film (GC/C-1) prepared by scraping and coating method showed excellent conductivity, which can reach 1000 S/cm. With the increase of the total number of alternating layers, the conductivity of the film shows a gradual decline, which is mainly because the increase of pores in the porous carbon alternating layer leads to the decrease of conductive path, which affects the increase of resistance caused by the free movement of electrons.…”
Section: Discussionmentioning
confidence: 99%
“…The polythiophene-derived nanocomposites had an EMI shielding efficiency of ~44 dB, along with 99% absorption at 11.65 GHz. The EMI shielding efficiency of polythiophene-based materials was improved due to conducting components in the nanocomposite, thereby resisting the undesirable radiations [120]. Furthermore, the thickness, magnetic features, as well as the electrical permittivity/permeability of polythiophene based shields were considered especially significant factors [117].…”
Section: Graphene Nanocomposites For Emi Shieldingmentioning
confidence: 99%
“…Although promising, as the properties (including the electrical conductivity, and as a result, the EMI performance) of polymer (nano)composites may be refined with the addition of functional conductive nanofillers (type(s), concentration, method of preparation, etc. ), the possible advantages of foaming such materials are undeniable [ 3 , 4 ]. Not only does foaming lead to even lighter structures, with direct advantages in fields such as aerospace, and enhanced functional characteristics such as reduced thermal conductivity, but it has also been proven to effectively reduce the percolation threshold of the conductive nanofillers, enabling lightweight components to be obtained, with high electrical conductivities at lower concentrations of nanofiller.…”
Section: Introductionmentioning
confidence: 99%